Exploring the experiences of children's palliative care for forced migrant families in the United Kingdom: an interpretative phenomenological study - Clancy, Marie; Bradbury-Jones, Caroline; Phillimore, Jenny; Taylor, Julie (Frontiers in Pediatrics, 2025)
IntroductionThis study focused on understanding the experiences of forced migrant families and the health care professionals who care for them within palliative care. Palliative care for children requires an active, holistic approach to care, with a focus upon improving quality of life. Forced migrant families encounter a range of additional challenges including the loss of family, belongings, and all sources of familiarity and support. The difficulties of navigating complex bureaucratic systems can confound access and communication difficulties.MethodsInterpretative Phenomenological Analysis methodology was used in this study to privilege participant perspectives and apply an active in-depth cyclical process of reflection and reflexivity. Advisory group members provided expertise in childhood illness, palliative care and forced migration, throughout the study. The Silences Framework offered novel theoretical and philosophical concepts, which helped to situate and prioritise the “silences” within the marginalised discourses of forced migration and palliative care. Seven family members and seven health care professional participants were interviewed from hospital, hospice and community palliative care settings in the UK.ResultsFour overarching themes were identified related to experiences of loss and grief, communication, faith and coping strategies and alienation and discrimination. Compassionate, empathetic, family-centred care which valued family belief systems and coping strategies, optimised care. Learning with and from families was described by all participants, which enhanced understanding and fostered mutual respect. However, barriers included poor access to services and resources, protocol-led care, limited time with families, communication barriers and staff burnout.DiscussionThe findings suggest the need for a specific educational pathway for palliative care professionals to include spiritual care provision, cultural humility, and moral reasoning. Interdisciplinary education including the use of lived-experience expert insights is also advocated. Sufficient time to build relationships, the importance of interpreter support and the need for better access to hospice care for forced migrant families is also recommended.